A practical guide to the diagnosis and management of suspected Non-tuberculous Mycobacterial Pulmonary Disease (NTM-PD) in the United Kingdom - D. J. Dhasmana; P. Whitaker; R. van der Laan; F. Frost (npj Primary Care Respiratory Medicine)
Abstract Non-tuberculous Mycobacterial Pulmonary Disease (NTM-PD) is a chronic disease characterised by progressive inflammatory lung damage due to infection by non-tuberculous mycobacteria (NTM). Global prevalence of NTM-PD is generally low but is rising, likely due to a combination of increased surveillance, increasing multimorbidity and improved diagnostic techniques. Most disease is caused by Mycobacterium avium complex species. NTM-PD can be challenging to both diagnose and manage but given the risk of untreated disease and the challenges around drug treatments, it is vital that all healthcare professionals involved in primary care consider NTM-PD at the earliest opportunity. In particular, NTM-PD should be considered where there are respiratory symptoms in the setting of pre-existing chronic lung disease such as chronic obstructive pulmonary disease (COPD) and bronchiectasis. Early suspicion should lead to appropriate primary screening measures. This article discusses the relevance of NTM-PD today, risk factors for developing disease, pathways from clinical presentation to referral to specialist care, and discusses management and drug treatments. A flow diagram of a screening process is presented as a guideline for best practice from a United Kingdom perspective.